Facile One‐Step Micropatterning Using Photodegradable Gelatin Hydrogels for Improved Cardiomyocyte Organization and Alignment. (28th December 2014) - Tsang, Kelly M. C.; Annabi, Nasim; Ercole, Francesca; Zhou, Kun; Karst, Daniel J.; Li, Fanyi; Haynes, John M.; Evans, Richard A.; Thissen, Helmut; Khademhosseini, Ali; Forsythe, John S.
Abstract : Hydrogels are often employed as temporary platforms for cell proliferation and tissue organization in vitro. Researchers have incorporated photodegradable (PD) moieties into synthetic polymeric hydrogels as a means of achieving spatiotemporal control over material properties. In this study protein‐based PD hydrogels composed of methacrylated gelatin and a crosslinker containing o ‐nitrobenzyl ester groups are developed. The hydrogels are able to degrade rapidly and specifically in response to UV light and can be photopatterned to a variety of shapes and dimensions in a one‐step process. Micropatterned PD hydrogels are shown to improve cell distribution, alignment, and beating regularity of cultured neonatal rat cardiomyocytes. Overall this work introduces a new class of PD hydrogel based on natural and biofunctional polymers as cell culture substrates for improving cellular organization and function. Abstract : A photodegradable hydrogel comprising a gelatin methacrylamide and an o ‐nitrobenzyl PEG crosslinker is utilized to create patterned substrates for tissue engineering. Photodegradation enables a facile method of creating striped patterns onto the gels. Patterned hydrogels are shown to improve the degree of alignment and beating regularity of cultured cardiomyocytes, showing promise for culture platforms with spatiotemporal control capabilities.